How Christian Universities Respond to Extremism - Robert A. Bowie; Lynn Revell (MDPI AG, 2018)
This research article explores how two English universities with Anglican foundations responded to UK government requirements to counter radicalization on campus. Semi-structured interviews were conducted with student union representatives, senior staff in the universities responsible for implementing the legal requirements and also those with special responsibility for religion. Christian foundation education institutions are required to implement government policy in response to visible radical and religious extremism. The UK higher education context is post-Christian (with lower levels of religious adherence) and post-secular (with greater plurality and greater prominence of controversial religious-related issues). It presents challenges for Christian university identity when meeting the complex concerns about dangers to students, university independence and free speech, and common values and public accountability. The research found that key to universities being able to respond effectively to the challenge of legal compliance and student welfare, was staff expertise in religion, but they have doubts about their capacity to respond effectively, and both staff and student have fears about this policy.